Alpha-methylacyl coenzyme A racemase overexpression in gallbladder carcinoma confers an independent prognostic indicator. Issue 4 (21st January 2012) - Wu, Li-Ching; Chen, Li-Tzong; Tsai, Yueh-Ju; Lin, Chun-Mao; Lin, Ching-Yih; Tian, Yu-Fang; Sheu, Ming-Juen; Uen, Yih-Huei; Shiue, Yow-Ling; Wang, Yu-Hui; Yang, Shu-Jing; Wu, Wen-Ren; et al.
Abstract : Aims: Increased β-oxidation of branched-chain fatty acids provides an additional metabolic advantage for cancer cells thereby enhancing tumour development and progression. Alpha-methylacyl coenzyme A racemase (AMACR) is an enzyme essential for the catabolism of branched-chain fatty acids that allows their subsequent β-oxidation and thus plays an important role in generating biological energy. However, the expression of AMACR has never been systemically investigated in gallbladder carcinoma. This study evaluated the expression status, associations with clinicopathological variables and prognostic implications of AMACR in a well-defined cohort of gallbladder carcinoma and confirmed their expression status in gallbladder carcinoma cells. Methods: AMACR immunostaining was assessable in 89 cases on tissue microarrays of gallbladder carcinoma, and it was correlated with clinicopathological factors and patient survival. In three gallbladder carcinoma cell lines and one non-tumorigenic cholangiocyte, AMACR mRNA expression was measured by real-time reverse transcription PCR and the endogenous expression of AMACR protein was analysed by western blotting. Results: AMACR overexpression was significantly associated with an advanced primary tumour status (p=0.027) and American Joint Committee on Cancer stage (p=0.027), an increased histological grade (p=0.002) and vascular invasion (p=0.017). Importantly, AMACR overexpression independently predicted worse disease-specific survival (p=0.0452, RR 1.887). Expression levels of AMACR mRNA and total protein in various cells were comparable. The abundance of AMACR expression increased in tumour cells and was even higher in the metastatic cell line. Conclusions: In primary gallbladder carcinoma, AMACR overexpression was correlated with important prognosticators and independently portended worse outcomes, highlighting the potential prognostic and therapeutic utility of AMACR in gallbladder carcinoma.